Vpx of simian immunodeficiency virus is localized primarily outside the virus core in mature virions. - Yu, X (1993)
Human immunodeficiency virus type 2 and the related simian immunodeficiency virus (SIV) contain a unique regulatory gene, vpx. The Vpx protein is packaged in mature virions and is required for efficient viral replication in peripheral blood lymphocytes and macrophages. To study the localization of Vpx in mature virions, conical and bar-shaped core structures of SIV from macaques (SIVmac) were purified. The SIVmac core has a density of approximately 1.25 g/cm3, compared with 1.16 g/cm3 for an intact virion. The relative proportions of major capsid protein (p27) and reverse transcriptase activity were similar for intact virions and core structures. The majority of matrix protein (p14) was removed from the purified core structure, suggesting its association with the viral membrane. Similarly, most of the Vpx protein was absent from the purified core structure. This result suggests that as with the matrix protein, the majority of Vpx proteins are localized outside the virus core. The localization of Vpx suggests that it may be involved in virus entry such as penetration or uncoating.